2022
DOI: 10.1186/s12937-022-00794-w
|View full text |Cite
|
Sign up to set email alerts
|

Healthy U.S.-style dietary patterns can be modified to provide increased energy from protein

Abstract: Background Dietary patterns developed by the USDA provide modest levels of protein (14–18% energy) within the Acceptable Macronutrient Distribution Range (AMDR) of 10–35% for adults, though diets providing a higher percentage of energy may be beneficial for some individuals. The purpose of this study was to determine if it is feasible to modify the Healthy U.S.-Style Eating Pattern (“HEP”) to provide a higher percentage of energy from protein. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…With the HPD modeled at 18% of calories as protein, there is flexibility to include a higher proportion of total calories as protein (including higher protein as beef), while still within the AMDR, which previous research has demonstrated can support improved health benefits including but not limited to weight management, physical function, and heart health [31][32][33][34]. In a recent analysis, researchers demonstrated the feasibility of modifying the amount of protein within the HDP by up to 25% of total calories while meeting all nutrient needs, using the framework implemented by the USDA in developing the HDP [16]. This supports the notion that individuals can have the flexibility to enjoy a variety of protein foods, including beef, and including intake of amounts greater than those modeled in the HDP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the HPD modeled at 18% of calories as protein, there is flexibility to include a higher proportion of total calories as protein (including higher protein as beef), while still within the AMDR, which previous research has demonstrated can support improved health benefits including but not limited to weight management, physical function, and heart health [31][32][33][34]. In a recent analysis, researchers demonstrated the feasibility of modifying the amount of protein within the HDP by up to 25% of total calories while meeting all nutrient needs, using the framework implemented by the USDA in developing the HDP [16]. This supports the notion that individuals can have the flexibility to enjoy a variety of protein foods, including beef, and including intake of amounts greater than those modeled in the HDP.…”
Section: Discussionmentioning
confidence: 99%
“…Item clusters are groupings of similar foods, in nutrient-dense form, used to calculate the nutrient profile of a food group or subgroup [15]. Proportional intakes of an item cluster based on a composite population-weighted average intake of the general U.S. population and/or varying life stage populations are the benchmarks for USDA dietary pattern models [15,16]. Using this approach, 3.7 ounce equivalents are modeled for the MPE of the HPD at the 2000-calorie level (Supplementary Figure S1).…”
Section: Calculation Of Beef-related Variablesmentioning
confidence: 99%
“…For each food reported in the WWEIA, the speci c USDA Food and Nutrient Database for Dietary Studies (FNDDS) converts the reported food use into the unit weight and composition required to control energy and nutrient intake. After the conversion, the dietary protein intake for day 1 was calculated [19]. WWEIA, details in https://www.cdc.gov/nchs/nhanes/wweia.htm .…”
Section: Dietary Protein Intake Assessmentmentioning
confidence: 99%